Evaluation of the maximum inscribed circle based on the maximum chord and maximum angle - Li, Xiuming; Yang, Peng; Yan, Yang; Liu, Guotong; Liu, Yuwei (Measurement science & technology, 2021)
The angle evaluation conditions, instead of maximizing the minimum radius, are proposed to deal with the maximum inscribed circle (MIC) based on a three-point model. According to the angle evaluation conditions, a corresponding chord-angle algorithm is given for evaluating the MIC by the maximum chord and its two maximum angles. Several examples have been carried out to assess the validity of the algorithms proposed.